Transaction-based industrial real estate price indices for Iskandar Malaysia - Chong, Tin Fook (2015)
Iskandar Malaysia is one of the fast growing special economic zones since established in 2006. The huge influx of investment which secured over RM160 Billion, especially on manufacturing sector has created enormous opportunity for demand on industrial real estate. Inspired by the call to have a more open, informative, transparent and sustainable real estate market growth in IM, it is therefore recommended to introduce industrial real estate price indices which are crucial for investment performance assessment and long run price trend tracking purpose. The study used 1,764 industrial real estate transaction data procured from NAPIC over 2005-2014. 2 pricing models have been employed to construct the industrial price indices for IM. Hedonic Regression Model (HRM) is conventional method as alternatively compared to Spatial Hedonic Model (SHM) which is statistically proven to be more superior by capturing the spatial correlation (adjacency effect) into the model. Robustness test on reliability and accuracy of the 2 price indices are also empirically substantiated that SHM is better than HRM with lower Mean Squared Error (MSE) and SEE (Standard Error Estimate). Out of Sample test also reveals that SHM has smaller price differences in between forecasted price versus actual transaction price throughout the study period. The Logical Test on regression coefficient signs postulate SHM is a reliable model for price forecasting in accordance to IM market norm.